A unified GPS-based earthquake catalog for the Sumatran plate boundary between 2002 and 2013 - Feng, Lujia (2015)
We have compiled the first self-consistent GPS-based earthquake catalog for the Sumatran plate boundary. Using continuous daily position time series from the Sumatran GPS Array (SuGAr), we document 30 earthquakes which occurred within or outside the SuGAr network from August 2002 through the end of 2013, and we provide estimates of both vertical and horizontal coseismic offsets associated with 1 M9.2, 3 M8, 6 M7, 19 M6, and 1 M5.9 earthquakes, as well as postseismic decay amplitudes and times associated with 9 M > 7 earthquakes and 1 M6.7 earthquake. For most of the previously studied earthquakes, our geodetic catalog provides more complete coseismic displacements than those published, showing consistent patterns of motion across a large range of distances. For many of the moderate to large earthquakes, we publish their coseismic displacements for the first time, providing new constraints on their locations and slip distributions. For the postseismic time series, we have tackled the challenge of separating the signals for individual events from the overlapping effects of many other earthquakes. As a result, we have obtained either new or much longer time series than previously published. Based on our long time series, we find logarithmic decay times ranging from several days to more than 20 years, and sometimes a second decay time is needed, suggesting that when studying large to great Sumatran earthquakes, we need to consider multiple postseismic mechanisms. Our geodetic catalog provides rich spatial and temporal Sumatran earthquake cycle information for future studies of the physics and dynamics of the Sumatran plate boundary.